Generalized models for unidirectional anisotropic properties of 3D printed polymers. Issue 8 (30th June 2020) - Nelson, Jared W.; Atkins, Dylan; Gottstine, Matthew L.; Yang, Jack; Garapic, Gordana; Jaminion, Stéphanie; Nelson, Aaron; Wilson, Katherine
Abstract : Purpose: The purpose of this paper is to empirically determine general models and methods for yield strength and modulus at different print orientations adequate for design purposes associated with typical fused deposition modeled (FDM) components/parts. Emphasis was placed on characterizing the impacts of anisotropy and resulting trends independent of material toward developing a method that matched the level of engineering required for current limited structural capabilities of FDM. Design/methodology/approach: Tensile tests were performed with a range of unidirectional filament orientations of three different materials allowing for determination of the generalized models, which are then compared to previous findings of others. Findings: Though anisotropic trends were similar to previous findings, minimum yield strength was found to be associated with filaments 75° from the loading direction resulting in a sinusoidal generalization. Modulus was found to be best approximated with an exponential decay. Resulting models allow for determination of yield strength and modulus in any orientation of FDM-printed material based on minimal testing. Originality/value: This study is the widest range of angles and materials to be tested and analyzed for unidirectional FDM allowing for new trends to be identified. In line with the level of engineering required for most FDM components/parts, the resulting generalized models allow for determination of yield strength and modulus with less computation and minimal testing.